NALISIS PENGARUH MODAL SENDIRI DAN MODAL PINJAMAN KREDIT USAHA RAKYAT (KUR) TERHADAP PENDAPATAN PENGUSAHA UMKM KABUPATEN TOBA SAMOSIR : STUDI KASUS PT BANK SUMUT CABANG BALIGE - Issabella Pratiwi Saragih; Syahrir Hakim Nasution (Departemen Ekonomi Pembangunan USU, 2015)
The objective of this research is to identify the correlation between Own Capital (X1) and Kredit Usaha Rakyat (KUR) (X2) of the Income Entrepreneurs UMKM (Y) Toba Samosir at PT Bank SUMUT Cabang Balige. The object of research is UMKM entrepreneurs Toba Samosir who is a debtor KUR at PT Bank SUMUT Cabang Balige period October 2014.Analyzer used in this research is to use multiple linear regression method. As for testing the measurement scale used by researchers using conformance test (Test Of Goodness Of Fit) is coefficient of determination (R-square) test T-statistics and statistical F-test using SPSS (Statistical Product and Service Solutions) 22.Based on the results of the study show that the Own Capital and Kredit Usaha Rakyat (KUR) positive correlation of the income entrepreneurs UMKM Toba Samosir.Keywords: Micro, Small and Medium Enterprises (UMKM), Kredit Usaha Rakyat (KUR)